Antioxidant Effect of Melatonin in Preterm Newborns. (19th November 2021) - Marseglia, Lucia; Gitto, Eloisa; Laschi, Elisa; Giordano, Maurizio; Romeo, Carmelo; Cannavò, Laura; Toni, Anna Laura; Buonocore, Giuseppe; Perrone, Serafina
Abstract : Introduction . Preterm infants are at risk of free radical-mediated diseases from oxidative stress (OS) injury. Increased free radical generation has been demonstrated in preterm infants during the first seven days of life. Melatonin (MEL) is a powerful antioxidant and scavenger of free radicals. In preterm neonates, melatonin deficiency has been reported. Exogenous melatonin administration appears a promising strategy in the treatment of neonatal morbidities in which OS has a leading role. Objective . The aim was to evaluate plasma MEL concentrations and OS biomarkers in preterm newborns after early administration of melatonin. Methods . A prospective, randomized double-blind placebo-controlled pilot study was conducted from January 2019 to September 2020. Thirty-six preterm newborns were enrolled. Starting from the first day of life, 21 received a single dose of oral melatonin 0.5 mg/kg once a day, in the morning (MEL group); 15 newborns received an equivalent dose of placebo (placebo group). Samples of 0.2 mL of plasma were collected at 24 and 48 hours after MEL administration. Plasma concentrations of melatonin, non-protein-bound iron (NPBI), advanced oxidation protein products (AOPP), and F2-isoprostanes (F2-Isopr) were measured. Babies were clinically followed until discharge. Results . At 24 and 48 hours after MEL administration, the MEL concentrations were significantly higher in the MEL group than in the placebo group (52759.30 ± 63529.09 vs. 28.57 ± 46.24 pg/mL and 279397.6 ± 516344.2 vs. 38.50 ± 44.01 pg/mL, respectively). NPBI and AOPP did not show any statistically significant differences between the groups both at 24 and 48 hours. At 48 hours, the mean blood concentrations of F2-Isopr were significantly lower in the MEL group than in the placebo group (36.48 ± 33.85 pg/mL vs. 89.97 ± 52.01 pg/mL). Conclusions . Early melatonin administration in preterm newborns reduces lipid peroxidation in the first days of life showing a potential role to protect high-risk newborns. Trial Registration . This trial is registered with NCT04785183, Early Supplementation of Melatonin in Preterm Newborns: the Effects on Oxidative Stress.